Legal Protection for Children who are Victims of The Crime of Rape - Ashylla Zabrina Dipayanti; Muchamad Iksan (Proceeding International Conference Restructuring and Transforming Law, 2023)
Children as members of the younger generation are a substitute for the country's independence aspirations and the potential for human resources for the founding of the country. Recently, sexual crimes against children have often occurred and the worst scenario is that sexual violence crimes now not only occur against adults but also children.Legal protection is the most important element in a legal state, because legal protection is the right of every citizen and the obligation of the state as the organizer of protection.applying normative juridical research methods, how to analyze library materials, namely primary and secondary legal materials. The threat to perpetrators of this rape, according to the criminal code regarding the crime of rape, is a maximum of 15 years. In fact, many perpetrators of rape do not receive the maximum sentence. Meanwhile, the victims have to carry stories of humiliation and psychological trauma for the rest of their lives. It's not fair.It is recommended that law enforcement officials protect children targeted for rape by safeguarding the victims' rights, so that the victims receive permanent mental and social rehabilitation. Request the government to provide facilities and infrastructure for the rehabilitation of child rape victims, so that the victims can continue their lives in the future. Suggestions for the community to help child victims of violence (rape) to be protected by law, so that Indonesia becomes a prosperous country for human-based welfare of the population.